2001
DOI: 10.1897/1551-5028(2001)020<2580:uommts>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Use of Molecular Markers to Study the Effects of Environmental Impacts on Genetic Diversity in Brown Bullhead (Ameirus Nebulosus) Populations

Abstract: Conservation biology needs sound biological information in order to maintain biological diversity in the face of the current rate of loss. An important component of the information needed is the level of genetic diversity within and between populations, especially for those species faced with exposure to environmental stressors. We applied multilocus DNA profile analysis (highly variable number tandem repeats [HVNTR] and randomly amplified polymorphic DNA [RAPD] techniques) and allozyme analysis to test whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…The susceptibility of fish to carcinogens is profoundly affected by genetic strain (Spitsbergen and Wolfe 1995). Murdoch and Hebert (1994) and Silbiger et al (2001) demonstrated a significant (p b 0.05) association of decreased genetic diversity, using multilocus DNA profile analysis, with exposure of brown bullhead to pollutants at impacted sites. Species differences certainly appear to play a role in neoplasia.…”
Section: Gendermentioning
confidence: 99%
“…The susceptibility of fish to carcinogens is profoundly affected by genetic strain (Spitsbergen and Wolfe 1995). Murdoch and Hebert (1994) and Silbiger et al (2001) demonstrated a significant (p b 0.05) association of decreased genetic diversity, using multilocus DNA profile analysis, with exposure of brown bullhead to pollutants at impacted sites. Species differences certainly appear to play a role in neoplasia.…”
Section: Gendermentioning
confidence: 99%
“…Creek chub are among the most common fishes in headwater streams throughout North America. Although fish populations may be abundant in ecological surveys, a history of periodic reductions in numbers could potentially reduce effective population size as detected using genetic markers in spatial comparisons with reference sites (Murdoch & Hebert, 1994;Silbiger et al, 2001). This hypothesis is further justified by the observation from an agriculturally dominated catchment that creek chub populations have been shown to exhibit several factors that contribute to population decline including reduced growth rates, delayed sexual maturity and reduced fecundity (Fitzgerald et al, 1999).…”
Section: Contemporary Land Use and Genetic Variationmentioning
confidence: 99%
“…Species that rely on freshwater habitats may be particularly vulnerable to population declines due to the disproportionate human use of catchment resources (Dudgeon et al, 2006). Human alteration of habitat, water quality and hydrology are interrelated factors that have been demonstrated to contribute to reduced genetic diversity in freshwater systems (Pringle, 1997;Silbiger et al, 2001;Geist & Kuehn, 2005;Blum et al, 2012) either through genetic drift or through natural selection. For these reasons, genetic variation has become a key assay of population status in studies of disturbed aquatic systems (Gillespie & Guttmann, 1999;Belfiore & Anderson, 2001;Bagley et al, 2002;Blum et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Old Woman Creek, located in north central Ohio, drains a primarily agricultural watershed (Matisoff et al, 2002). This site has been used extensively as a reference site for studies of environmental impacts on brown bullhead (Baumann et al, 1990;McFarland et al, 1999;Lin et al, 2001;Silbiger et al, 2001;Yang et al, 2003). However, metals and agricultural runoff (Klarer, 1988) as well as low PAH contaminants near bridges with creosote-treated wood (Johnston and Baumann, 1989;Lin et al, 1994) have been reported.…”
Section: Potential Reference Sitesmentioning
confidence: 99%